2012
DOI: 10.1210/jc.2012-2325
|View full text |Cite
|
Sign up to set email alerts
|

Boys with Undescended Testes: Endocrine, Volumetric and Morphometric Studies on Testicular Function before and after Orchidopexy at Nine Months or Three Years of Age

Abstract: Morphometric and volumetric data show that orchidopexy at 9 months is more beneficial for testicular development than an operation at 3 yr of age. Testicular volume was furthermore shown to reflect germ cell numbers in early childhood, whereas endocrine parameters could not predict cellular structure of the testis or its spontaneous descent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
84
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 107 publications
(93 citation statements)
references
References 33 publications
5
84
0
4
Order By: Relevance
“…After hand‐searching of the reference lists of the 12 eligible studies identified from database searching, a further three eligible studies were identified. In total, 15 published studies9 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38 were included in the review ( Fig . 1 and Table  1).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…After hand‐searching of the reference lists of the 12 eligible studies identified from database searching, a further three eligible studies were identified. In total, 15 published studies9 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38 were included in the review ( Fig . 1 and Table  1).…”
Section: Resultsmentioning
confidence: 99%
“…1 and Table  1). Of the 15 papers, four by Kollin and co‐workers25, 26, 27, 28 were based on the same population of infants, and papers by Feyles et al 29. and Canavese and colleagues9 30, 31 also had overlapping populations.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations